From Garfield to Harding : the success of midwestern front porch campaigns - Bourdon, Jeffrey Normand (The Kent State University Press, 2019)
"In 1880, James Garfield faced an important question as a presidential candidate--should he stump for office and stay quiet like most 19th Century contestants, or try something else. He decided to try something new and meet voters at his farm. By the end of the campaign, thousands of people, including naturalized voters, African Americans, women, men from various occupations, and young voters traveled to Garfield's home, listened to him speak, shook hands, met his family, and were invited inside. The press reported the interactions across the country. Not only did Garfield win, he started a new campaign technique that carried three other Republicans to victory. Benjamin Harrison followed suit in 1888 and his crowds dwarfed Garfield's as Indianapolis exploded with hundreds of thousands of visitors. Eight years later, William McKinley ran the most famous front porch campaign in his hometown of Canton, Ohio. Seven hundred and fifty thousand Americans paraded down the streets including miner's unions, women's suffrage groups, and Confederate soldiers to their Union counterparts. Finally, Warren Harding continued the tradition in his 1920 campaign and won by a sixty percent popular majority. Using a technique very evident today, Republican campaign managers quickly realized that merchandising their candidate as a brand generated much support. While no candidate lost campaigning this way, after Harding, presidential candidates traveled the country to speak to the American people"--